Impact analysis of rotavirus vaccination in various geographic regions in Western Europe. Issue 45 (29th October 2021) - Verberk, J.D.M.; van Dongen, J.A.P; van de Kassteele, J.; Andrews, N.J.; van Gaalen, R.D.; Hahné, S.J.M.; Vennema, H.; Ramsay, M.; Braeckman, T.; Ladhani, S.; Thomas, S.L.; Walker, J.L.; et al.
Abstract: Background: Universal mass vaccination (UMV) against rotavirus has been implemented in many but not all European countries. This study investigated the impact of UMV on rotavirus incidence trends by comparing European countries with UMV: Belgium, England/Wales and Germany versus countries without UMV: Denmark and the Netherlands. Methods: For this observational retrospective cohort study, time series data (2001–2016) on rotavirus detections, meteorological factors and population demographics were collected. For each country, several meteorological and population factors were investigated as possible predictors of rotavirus incidence. The final set of predictors were incorporated in negative binomial models accounting for seasonality and serial autocorrelation, and time-varying incidence rate ratios (IRR) were calculated for each age group and country separately. The overall vaccination impact two years after vaccine implementation was estimated by pooling the results using a random effects meta-analyses. Independent t-tests were used to compare annual epidemics in the pre-vaccination and post-vaccination era to explore any changes in the timing of rotavirus epidemics. Results: The population size and several meteorological factors were predictors for the rotavirus epidemiology. Overall, we estimated a 42% (95%-CI 23;56%) reduction in rotavirus incidence attributable to UMV. Strongest reductions were observed for age-groups 0-, 1- and 2-years (IRR 0.47, 0.48 and 0.63, respectively). No herd effect induced by UMV in neighbouring countries was observed. In all UMV countries, the start and/or stop and corresponding peak of the rotavirus season was delayed by 4–7 weeks. Conclusions: The introduction of rotavirus UMV resulted in an overall reduction of 42% in rotavirus incidence in Western European countries two years after vaccine introduction and caused a change in seasonal pattern. No herd effect induced by UMV neighbouring countries was observed for Denmark and the Netherlands.